Can foods produced with new plant engineering techniques succeed in the marketplace? A case study of apples. Issue 1 (21st November 2021) - Marette, Stéphan; Beghin, John; Disdier, Anne‐Célia; Mojduszka, Eliza
Abstract: We present a model for research and development (R&D) investment in food innovations based on new plant engineering techniques (NPETs) and traditional hybridization methods. The framework combines uncertain and costly food innovation with consumers' willingness to pay (WTP) for the new food. The framework is applied with elicited WTP of French and US consumers for new improved apples. NPETs may be socially beneficial under full information and when the probability of success under NPETs is relatively high. Otherwise, the traditional hybridization is socially optimal. A probable collapse of conventional apples raises the social desirability of new apples generated by NPETs and traditional hybridization.